Tissue-engineered ribs for chest wall reconstruction: a case with 12-year follow-up. (July 2014) - Xie, Hui-Qi; Huang, Fu-Guo; Zhao, Yong-Fan; Qin, Ting-Wu; Li, Xiu-Qun; Liu, Chang; Li-Ling, Jesse; Yang, Zhi-Ming
We hereby report on a case in which a huge chest wall defect generated by resection of a massive aggressive tumor (desmoplastic fibroma) was repaired with osteogenic-induced mesenchymal stem cells embedded in a bone-derived biomaterial. In this case, there were three challenges to overcome: reconstruction of the soft tissue, repair of the skeletal defect of the thoracic wall and repair of the defect in the pleural cavity. The defects of soft tissue and pleural cavity were reconstructed, respectively, with an ipsilateral abdominal flap and a diaphragm muscular flap. The huge defect in the chest wall was successfully repaired with the tissue-engineered ribs, which was confirmed by long-term follow-up with computerized tomography and histological and immunohistochemical evaluations. In view of its effectiveness and safety, tissue-engineered bones may have a broad application for the repair of large skeletal defects and bone regeneration.